Tracking systems in team sports: back to basics - Torres-Ronda, L.; Clubb, J.; Beanland, E. (Sport Performance & Science Reports, 2022)
The desire to deepen the understanding of sports perfor mance has led to the proliferation of technology. Within this, tracking technology enables the objective capture of work completed by athletes independent of their internal charac teristics, which is labelled external load (1). Such data en ables practical applications that include quantifying physical demands, objectifying training prescription, monitoring indi vidual training load, and assisting with rehabilitation